The Influence of Work Motivation, Work Discipline, and Work Environment on the Performance of Generation Z Employees at Coffee Shops in Kuningan City - Hafiyyana Prayoga faza Qinthara; Edy Hartono (Publikasi Indonesia, 2026)
This research aims to analyze the influence of work motivation, work discipline, and work environment on the performance of Generation Z employees in coffee shops in Kuningan City. This research uses a quantitative approach with associative design and multiple linear regression analysis. The research population was Generation Z employees who work in various coffee shops in Kuningan City. Data was collected through questionnaires using the Likert scale and analyzed using the SPSS program. The analysis included validity, reliability, classical assumption tests, and hypothesis testing through t-tests, F tests, and determination coefficients. The results show that work motivation, work discipline, and work environment have a positive and significant influence on employee performance. Work motivation was the most dominant variable with a regression coefficient of 0.367, followed by work environment of 0.351 and work discipline of 0.187. Simultaneously, these three variables contributed 72.9% to the variation in employee performance. The results of this study provide recommendations for coffee shop managers to increase employee work motivation through an appropriate reward system, create a conducive work environment, and strengthen the application of work discipline to improve the performance of Generation Z employees. This research contributes to the study of human resource management by highlighting the factors that affect the performance of Generation Z employees, especially in the coffee shop industry in Kuningan City which is still limited in research.